Karakteristik Fisikokimia, Organoleptik dan Angka Kecukupan Gizi Snack Bar Berbahan Dasar Sorgum dengan Penambahan Sari Kurma dan Madu - Cahya, Salsabilla Aulia; Wahyudi, Vritta Amroini; Warkoyo, Warkoyo (Food Technology and Halal Science Journal, 2025)
Snack bar is a snack with complex nutritional content consisting of a mixture of various food ingredients compacted into a bar shape. Addition of date paste and honey is used as binders to enhance flavor and nutritional value. This research aims to determine the physicochemical characteristics, organoleptic properties, and Nutrient Adequacy Score (NAS) of sorghum-based snack bars with added date paste and honey. The study employed a Randomized Complete Block Design (RCBD) with one factor, date paste and honey, consisting of 6 treatments (0:50 g; 10:40 g; 20:30 g; 25:25 g; 30:20 g; 40:10 g) and 3 replications. The results showed that increasing honey content in snack bars increased moisture and carbohydrate levels, whereas increasing date paste content increased protein and fat levels, as well as hardness texture in the snack bars. The best treatment for the snack bars was found in treatment F5 with 40 g date paste and 10 g honey, with moisture content of 9.97%, ash content of 0.93%, protein content of 4.75%, fat content of 13.35%, carbohydrate content of 70.99%, and hardness of 23.83 N. The NAS values for the best treatment of snack bars per serving size (25 g) were 2% protein, 5% fat, and 5% carbohydrates, with a total energy value of 105.3 Kcal. The different ratios of date paste and honey significantly affected the scoring attributes of color, aroma, taste, and texture.